Olfactory and Gustatory Dysfunction in Patients With Autoimmune Encephalitis - Geran, Rohat; Uecker, Florian C.; Prüss, Harald; Haeusler, Karl Georg; Paul, Friedemann; Ruprecht, Klemens; Harms, Lutz; Schmidt, Felix A. (Frontiers in Neurology, 2019)
Objective: To test the hypothesis that olfactory (OF) and gustatory function (GF) is disturbed in patients with autoimmune encephalitides (AE). Methods: The orthonasal OF was tested in 32 patients with AE and 32 age- and sex-matched healthy controls (HC) with the standardized Threshold Discrimination Identification (TDI) score. This validated olfactory testing method yields individual scores for olfactory threshold (T), odor discrimination (D) and identification (I), along with a composite TDI score. The GF was determined by the Taste Strip Test (TST). Results: Overall, 24/32 (75 %) of patients with AE, but none of 32 HC (p < 0.001) had olfactory dysfunction in TDI testing. The results of the Threshold-, Discrimination and the Identification subtests were significantly reduced in patients with AE compared to HC (all p<0.001). Assessed by TST, 5/19 (26.3 %) of patients with AE, but none of 19 HC presented a significant limitation in GF (p < 0.001). The TDI score was correlated with the subjective estimation of the olfactory capacity on a visual analogue scale (VAS; rs = 0.475, p = 0.008). Neither age, sex, modified Rankin Scale nor disease duration were associated with the composite TDI score. Conclusions: This is the first study investigating OF and GF in AE patients. According to unblinded assessment, patients with AE have a reduced olfactory and gustatory capacity compared to HC, suggesting that olfactory and gustatory dysfunction are hitherto unrecognized symptoms in AE. Further studies with larger number of AE patients would be of interest to verify our results.